ASSESSMENT OF THE MOMENT OF STABILITY WHEN PROVIDING FRONTAL STABILITY OF THE EXOSKELETON - Andrianov, Yuri; Fishchenko, Pyotr; Kapustin, Alexander (Journal of Applied Engineering Science, 2019)
In medical exoskeletons, it is necessary to support a stable vertical position of a person. Based on the use of mathematical modeling and theoretical mechanics methods, estimation of the moment of stability is performed while ensuring the frontal (lateral) stability of a person in a medical exoskeleton. This will allow to receive the maximum allowable safe speed, eliminating the fall in the frontal plane. Recommendations for providing frontal (lateral) stability are given.